The role of stress and sleep disorders in the development of cardiovascular complications in patients with arterial hypertension: what is important for an internist to know? A review - Valery A. Ionin (ZAO "Consilium Medicum", 2023)
This publication discusses the mechanisms underlying the development of arterial hypertension on the background of stress, discusses the current problems of blood pressure control in patients with stress-induced sleep disorders, the clinical features of patients with hypersympathicotonia as the main mechanism for the development of arterial hypertension and blood pressure variability in patients with comorbid pathology, a diagnostic algorithm, as well as presenting current recommendations in the strategy for choosing the optimal antihypertensive therapy with the possibility of personalized choice in various clinical situations.